Secular stagnation in the framework of rentier-financier capitalism and globalization - Bresser-Pereira, Luiz Carlos (2017)
Rentier-financier capitalism, neoliberalism and globalization have been in a crisis since 2008. It is characterized by low growth rates, quasi-stagnant wages and increase of inequality since rentiers replaced business entrepreneurs, neoliberalism became the hegemonic ideology, and globalization became the means to achieve the best of all possible worlds. But the rich capitalist world faces the threat of secular stagnation. In this paper, I discuss this threat, the main authors that have been discussing it, and the new historical facts that are behind such threat. Among the threats are the fall of the productivity of capital associated with information and communication technology, the increase of monopoly power, the profusion of capitals, and globalization, which opened room for the competition of developing countries.